Green Extraction of Kleinhovia hospita Saponins: Superiority of Microwave Irradiation over Maceration and the Critical Role of Solvent Polarity - Hikmawan, Baso Didik; Khotimah, Khusnul; Permana, Mutia Ramadhani Rose; Ahmad, Islamudin; Febrina, Lizma; Arifuddin, Muhammad; Ibrahim, Arsyik; Salam, Supriatno (Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, 2025)
Kleinhovia hospita is a hepatoprotective plant rich in bioactive saponins, yet conventional extraction methods remain inefficient. This study aimed to optimize saponin recovery by comparing Microwave-Assisted Extraction (MAE) against conventional maceration and assessing the effect of solvent polarity. Saponins were extracted using MAE (15 minutes) and maceration (72 h) with various ethanol concentrations ranging from 0 to 96%. Total Saponin Content (TSC) was quantified colorimetrically using the vanillin-sulfuric acid method. MAE significantly outperformed maceration, attaining a two-fold increase in saponin purity (106.67 and 52.92 mg Diosgenin Equivalent (DE)/g extract, respectively) in a fraction of the time. Solvent analysis revealed a trade-off: whereas 96% ethanol yielded the highest specific purity (133.89 mg DE/g), it resulted in low mass recovery. In contrast, 50% ethanol extracted the highest Total Saponin Yield (TSY) (18.84 mg/g powder), effectively balancing matrix swelling with solubility. MAE utilizing 50% ethanol is identified as the optimal, rapid, and green strategy for the industrial production of standardized K. hospita extracts.